Kinetics of Separate Hydrolysis and Fermentation of Chlorella in Bioethanol Production - Megawati; Astuti W.; Triwibowo B.; A S Bahlawan Z.; A P Bancin W.; R Daksana M.; Indriasari H.; Maulidia M. (E3S Web of Conferences, 2024)
The objective of this research is to study the hydrolysis kinetics of Chlorella using alpha-amylase and gluco-amylase as well as the fermentation kinetics of its hydrolysate using yeast. Hydrolysis was done on microalgae concentration of 60 g/L, pH of 6, and various temperatures and gluco-amylase volumes. A pretreatment using alpha-amylase was carried out before hydrolysis using gluco-amylase. Fermentation was done using various yeast mass and pH. The kinetics model used was fractal model by Valjamae. Valjamae model could quantitatively describe enzymatics hydrolysis of Chlorella really well. At hydrolysis 50°C, the fractal exponential value is 0.57 and reaction rate constant is 0.63, 0.70, and 0.76 1/h, at gluco-amylase volumes of 1,2, and 3% v/v. Temperature influence follows the Arrhenius law with an activation energy of 10.644 kJ/mol and frequency factor of 25.5 1/hour. During fermentation, the higher the pH, the higher the reaction rate constant, from pH 3 to 6, the values rise from 0.22 to 0.25 1/hour. In addition, because yeast mass increases from 0.25 to 1 g, the values also increase from 0.27 to 1.45 1/hour.